2021
DOI: 10.3390/ijerph18062834
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-Leptospiral Activity of Phyllanthus amarus Extracts and Their Combinations with Antibiotics

Abstract: Despite modern medicine, there is an increasing trend for cases of the bacterial infection leptospirosis, and this has led to the exploration of alternative medicines from various sources including plants. The aim of this study was to investigate the in vitro anti-leptospiral activity of Phyllanthus amarus extracts alone and combined with penicillin G, ceftriaxone, and doxycycline. Antimicrobial susceptibility testing was performed using the microdilution broth technique upon methanol extract (ME), aqueous ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…It is a default process to identify and analyze docking introduction in drug discovery and forms the basis for the design and analysis of novel drugs against a specific target protein [ 36 ]. Several studies have reported the use of molecular docking to understand the probable mechanism of action for various drugs, including antimicrobial agents [ 37 ]. The degree of protein–ligand complex interaction is commonly referred to as the binding affinity in molecular docking investigations.…”
Section: Discussionmentioning
confidence: 99%
“…It is a default process to identify and analyze docking introduction in drug discovery and forms the basis for the design and analysis of novel drugs against a specific target protein [ 36 ]. Several studies have reported the use of molecular docking to understand the probable mechanism of action for various drugs, including antimicrobial agents [ 37 ]. The degree of protein–ligand complex interaction is commonly referred to as the binding affinity in molecular docking investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been a number of studies using phages in the prevention and treatment of plant and animal diseases [2][3][4]. Besides, there are also many studies on plant extracts with high antimicrobial efficiency [5], especially Phyllanthus amarus [6,7]. Bacteriophages and P. amarus are considered potential biological agents in the treatment of bacterial diseases in aquatic animals.…”
Section: Introductionmentioning
confidence: 99%